Chief Executive Compensation and Corporate Groups in Japan: New Evidence from Micro Data - Takao Kato (Levy Economics Institute of Bard College, 1994)
This paper begins with addressing a simple empirical question: how much Japanese executives earn. By presenting the first systematic review of prior studies reporting the mean level of Japanese executive compensation, I conclude that the best available answer to this empirical question is that the average salary and bonus of CEOs of large Japanese firms during 1980s is between 30 to 45 million yen, roughly one third of what the US counterparts earn in salary and bonus. In reaching this conclusion, I also identify three major data sources available for empirical studies of Japanese executive compensation and discuss the strengths and weaknesses of each data source. The rest of the paper is devoted to a more analytical question: What is the relationship between executive compensation and financial corporate groups in Japan, an issue that has not been previously investigated. By using micro data on CEO compensation of 154 large Japanese firms consisting of 116 group-affiliated firms and 38 independent firms, I find that CEOs of group firms earn 20 to 30 % less than those of independent firms, after controlling for shareholder returns, accounting measures of profitability, alternative firm objective measures such as size and capital investment, and personal characteristics of CEOs. I also find that alternative firm objectives, measured by employment and capital investment, are more relevant to the determination of CEO compensation of group firms than that of independent firms. These findings are consistent with the recent contributions in the literature of Japanese corporate governance stressing the role of banks as monitoring agents and suggesting that managers of group firms represent not only the interest of shareholders but the interest of main banks.
Keywords: 330